2020
DOI: 10.1038/s41386-020-0692-1
|View full text |Cite
|
Sign up to set email alerts
|

A novel multidimensional reinforcement task in mice elucidates sex-specific behavioral strategies

Abstract: A large body of work has focused on understanding stimulus-driven behavior, sex differences in these processes, and the neural circuits underlying them. Many preclinical mouse models present rewarding or aversive stimuli in isolation, ignoring that ethologically, reward seeking requires the consideration of potential aversive outcomes. In addition, the context (or reinforcement schedule under) in which stimuli are encountered can engender different behavioral responses to the same stimulus. Thus, delineating n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 36 publications
2
22
0
Order By: Relevance
“…To disentangle multiple task parameters (e.g., valence, action initiation, prediction 33 ), we used the recently developed multidimensional cue outcome action task (MCOAT) 34 in combination with the genetically encoded dopamine sensor, dLight1.1, 35 to record in vivo dopamine dynamics in the NAc core (Figures S1A-S1D). We trained mice in a positive reinforcement task, in which an auditory cue predicted that an operant response would result in the delivery of sucrose (positive reinforcement) (Figures 1A and 1B).…”
Section: Dopamine Release Does Not Track Rpe In Aversive Contextsmentioning
confidence: 99%
See 1 more Smart Citation
“…To disentangle multiple task parameters (e.g., valence, action initiation, prediction 33 ), we used the recently developed multidimensional cue outcome action task (MCOAT) 34 in combination with the genetically encoded dopamine sensor, dLight1.1, 35 to record in vivo dopamine dynamics in the NAc core (Figures S1A-S1D). We trained mice in a positive reinforcement task, in which an auditory cue predicted that an operant response would result in the delivery of sucrose (positive reinforcement) (Figures 1A and 1B).…”
Section: Dopamine Release Does Not Track Rpe In Aversive Contextsmentioning
confidence: 99%
“…Our previous studies showed the order of the positive and negative reinforcement training did not change the behavioral performance. 34 A second auditory discriminative stimulus (S d,shock ) -either tone or white noise, counterbalanced across animals and trial types -was presented at the beginning of each trial following a variable ITI as described above. In each trial the discriminative stimulus was presented for 30 s after which a series of 20 footshocks (1mA, 0.5 s duration) was delivered with a 15 s inter-stimulus interval.…”
Section: Negative Reinforcementmentioning
confidence: 99%
“…Few rodent studies to date have examined sex differences in opioid taking or reinstatement. In a study investigating non–addiction-related reinforcement processes, female mice were biased toward negative reinforcement relative to positive reinforcement, in which females responded more to avoid an aversive shock than to receive a sucrose reward and were more sensitive to punishment than males ( 70 ). Female rodents more rapidly acquired morphine and heroin self-administration ( 22 , 71 , 72 ), self-administered more intravenous heroin ( 22 ) and fentanyl vapor ( 23 ) in long-access self-administration sessions, consumed more oral oxycodone during self-administration ( 73 , 74 ), and had higher motivation for fentanyl ( 75 ) than males.…”
Section: Cues Associated With Negative Reinforcement Learningmentioning
confidence: 99%
“…As many have reported previously, in rodents, females are more motivated to self-administer both natural reinforcers and cocaine, suggesting that females may be more vulnerable to the reinforcing properties of drugs, especially stimulants (Becker et al, 2017). Further, differences in motivation for natural reinforcers suggest key differences between males and females at baseline that could interact with drug-induced plasticity to alter the trajectory of cocaine-induced changes within the brain (Kutlu et al, 2020). To investigate this sexual dichotomy, E.S.C.…”
Section: Epigenetic Priming Supports Persistent Changes In Activityinduced Transcriptionmentioning
confidence: 69%